New Ediacara fossils preserved in marine limestone and their ecological implications - Chen, Zhe (Nature Publishing Group, 2014)
Ediacara fossils are central to our understanding of animal evolution on the eve of the Cambrian explosion, because some of them likely represent stem-group marine animals. However, some of the iconic Ediacara fossils have also been interpreted as terrestrial lichens or microbial colonies. Our ability to test these hypotheses is limited by a taphonomic bias that most Ediacara fossils are preserved in sandstones and siltstones. Here we report several iconic Ediacara fossils and an annulated tubular fossil (reconstructed as an erect epibenthic organism with uniserial arranged modular units), from marine limestone of the 551–541 Ma Dengying Formation in South China. These fossils significantly expand the ecological ranges of several key Ediacara taxa and support that they are marine organisms rather than terrestrial lichens or microbial colonies. Their close association with abundant bilaterian burrows also indicates that they could tolerate and may have survived moderate levels of bioturbation.